Arthroscopic excision of osteoid osteoma of the talus: A case report - Kumar Jha, Amit; kumar jagannathan, Saravana; Kumar Singh, Santhosh; Patel, Swaroop; Tiwari , Saurabh; Yadav, Mukesh (Journal of the Foot & Ankle, 2026)
Osteoid osteomas are among the common benign bone tumors. They typically found in the cortex of long tubular bones, causing characteristic night pain and significant disability. They are commonly found in younger males characterized by lesions with vascularized nidus surrounded by sclerotic bone. They rarely affect talus. Due to their subtle presentation, they are often missed during clinical examination and on plain radiographs. Computed tomography (CT) is essential for accurate diagnosis. Recently, CT guided radiofrequency ablation has become the preferred treatment. In this article, we present a case of large osteoid osteoma of the talar neck with associated impingement. We utilized arthroscopy to identify the subarticular lesion by its characteristic wine-red colour and performed curettage of both the lesion and the osteophyte in a single procedure. At six months follow-up, patient reported complete pain relief with improved ankle range of motion. Level of evidence IV; Therapeutic study; Case report.